Perception of work conditions and occupational stress among civil and military police officers of special operations units Percepção das condições de trabalho e estresse ocupacional em policiais civis e militares de unidades de operações especiais - Cardoso T.E.* (2018)
© 2018 Brazilian Journal of Occupational Therapy.All right reserved.Introduction: Adverse working conditions are inherent in the police service and might have a negative impact in the physical and mental health of these professionals, interfering also in their work practice. Objective: To analyze the perception of working conditions and the occupational stress among civil and military police officers of the special operations units of Santa Catarina. Method: Participants were 84 civil and military male police officers, with mean age of 34.68 (sd = 6.00) years, acting in the special operations units (BOPE, COPE, SAER, and BAPM). The information about the perception of working conditions were collected using the Environment and Working Conditions Profile questionnaire, and information about occupational stress were collected using Job Stress Scale. Results: The perception of working conditions related to total score were 24.12 points, with social environment (6.92 points) the component with the highest score, and remuneration and benefits (4.50 points) the component with the lowest score. In relation to occupational stress, more than a half of the police officers identified their work as low demand, low control, and low social support. Moreover, almost a half (42.2%) of the police officers had their work classified as active. A negative correlation between working conditions and occupational stress was found. Conclusion: Civil and military police officers demonstrated a regular perception of their working conditions, and a worse perception related to remuneration and benefits and physical environment. One in four police officers performs passive and high-wear work, considered to be at a greater risk of illness.